Trust in digitalization and artificial intelligence: Insights from qualitative research on online parenting programs - Yunike, Yunike; Rehana, Rehana; Misinem, Misinem; Kusumawaty, Ira (Institute of Computer Science (IOCS), 2024)
Parenting in the digital era is experiencing significant changes with the presence of online training platforms that utilize artificial intelligence (AI). Although digitalization offers the potential to improve the quality of care, challenges related to trust in technology are important issues that need to be researched. This research aims to explore how trust in digitalization and AI influences the adoption and effectiveness of online parenting training. This research method is qualitative, using in-depth interviews as a data collection technique with parents and online parenting training providers. Data were analyzed using thematic analysis techniques to identify main patterns and themes. The research results show that users' level of trust in digital technology and AI has a direct impact on their readiness to participate in and implement parenting training. Parents who have high trust are more active and successful in utilizing the training, whereas those who are skeptical face difficulties in implementing the material. In conclusion, trust in technology is a key factor in the success of online parenting training. This research highlights the importance of building trust through transparent and quality program design to increase training effectiveness.